2015
DOI: 10.1111/pcmr.12352
|View full text |Cite
|
Sign up to set email alerts
|

Melanoma tumors frequently acquire LRP2/megalin expression, which modulates melanoma cell proliferation and survival rates

Abstract: Subscribe to PCMR and stay up-to-date with the only journal committed to publishing basic research in melanoma and pigment cell biology As a member of the IFPCS or the SMR you automatically get online access to PCMR. Sign up as a member today at www.ifpcs.org or at www.societymelanomaresarch.org If you wish to order reprints of this article, please see the guidelines here Submit your next paper to PCMR online at http://mc.manuscriptcentral.com/pcmr Summary We show that the multiligand receptor megalin, known t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
40
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 48 publications
6
40
0
Order By: Relevance
“…52 The IGF-1 and EGF growth factors known to promote placental development and growth as well as fetal growth 5 are both established ligands for megalin, 15,16 and a recently published study of megalin function in melanoma cells revealed that megalin may be involved in modulation of IGF-1 signaling in these cells. 26 In the context of growth factor signaling, MVBs were previously shown to play key roles in the control of growth factor signaling (e.g., EGF signaling), 53 and interestingly, we observed megalin on the luminal vesicles of MVBs as well as their outer limiting membrane in cytotrophoblasts of first trimester and term placenta. To our knowledge, megalin has not previously been identified in MVBs.…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations
“…52 The IGF-1 and EGF growth factors known to promote placental development and growth as well as fetal growth 5 are both established ligands for megalin, 15,16 and a recently published study of megalin function in melanoma cells revealed that megalin may be involved in modulation of IGF-1 signaling in these cells. 26 In the context of growth factor signaling, MVBs were previously shown to play key roles in the control of growth factor signaling (e.g., EGF signaling), 53 and interestingly, we observed megalin on the luminal vesicles of MVBs as well as their outer limiting membrane in cytotrophoblasts of first trimester and term placenta. To our knowledge, megalin has not previously been identified in MVBs.…”
Section: Discussionmentioning
confidence: 57%
“…7A, term placenta megalin and JAR cellderived megalin were both recognized by the purified anti-megalin antibody previously used for studies of human renal and melanoma megalin. [24][25][26] Also, the molecular weight of term placenta megalin and JAR cell-derived megalin was similar to that of renal megalin (Fig. 7A).…”
Section: Biochemical Characterization Of Placental Megalinmentioning
confidence: 85%
See 2 more Smart Citations
“…LRP2 is a component and an auxiliary Hedgehog signaling receptor (30). Andersen et al (31) reported that LRP2 regulated melanoma cell proliferation and survival rates, and that knocking down LRP2 induced apoptosis. LRP2 may serve a similar function in colorectal cancer.…”
Section: Characteristics Of the Eight Csc-associated Genesmentioning
confidence: 99%